AN INTEGRATED APPROACH OF GRA COUPLED WITH PRINCIPAL COMPONENT ANALYSIS FOR FRICTION STIR WELDED AM20 MAGNESIUM ALLOY - Prasetya, Ichwanul Kahfi; Rifki, Kevin Agung Fernanda; Ahsan, Muhammad (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
Magnesium alloys possess highly desirable properties and become increasingly popular in various practical applications due to their lightweight nature as a replacement for aluminum alloys. The purpose of this study is to optimize the process parameter to get the better mechanical properties of friction stir welded AM20 magnesium alloy using Taguchi Grey relational analysis (GRA) Coupled with Principal Component Analysis (PCA). The considered process parameters are plunging depth (PD), tool rotation speed (RPM), and welding speed (WS), shoulder diameter (SD), and. The experiments were carried out by using Taguchi's L18 factorial design of experiment. The processes parameters were optimized and ranked the parameters based on the W-GRG. The responses are ultimate tensile strength (UTS), yield strength (YS), percentage of elongation (% E), compressive stress (CS), bending angle, average hardness at the nugget zone (NZ), thermo mechanical affected zone (TMAZ) and heat affected zone (HAZ). Case-1 is preferable when high values of quality parameters are desired, while Case-2 is more suitable when some parameters needs to be low values. The optimal combination of parameters in case-1 is PD1, RPM3, WS3, and SD1, while the optimal combination of parameters in case-2 is PD1, RPM1, WS2, SD1. In both cases, the most influence response in is UTS, while the maximum influence of factor is SD. We suggest further research to be able to use confirmatory experiments so that we can find out how well the new setup is suggested.